Web-Based Online Food Sales Information System: Sistem Informasi Penjualan Makanan Online Berbasis Web - Ayyubi, Rizky Al; Astutik, Ika Ratna Indra (Indonesian Journal of Innovation Studies, 2022)
Warung Bebek Srundeng is a business place that serves a variety of food menus, drinks and snacks sold in general to the publics. So far the stalls have not applied technology in terms of queues and buyer’s order. This is less than maximum for the queue of buyers. The stalls must also manually record the buyer’s order. From the above problems, the writer made a Web-Based Online Food Sales Information Systems. An information system that makes it easy for buyer’s to order food and makes it easy for stalls to view order data from buyer’s without having to manually record orders. The system design uses PHP programming language with MySQL as database management. With this information system, is expected to maximize sales in the stall, and make it easier for buyers to order food in the stall.